The Implementation of the Process Writing Method in Teaching Arabic Writing at Islamic Senior High Schools: Teachers’ and Students’ Perspectives - Nayli Shofiel ‘Uyun; Reiqi Aisya Epa; Naufal Wirafyta Ramadhan (Gunung Djati Conference Series, 2026)
This study aims to investigate how teachers plan and implement the Process Writing method in Arabic writing instruction at Islamic Senior High Schools (MA); how students respond, experience, and engage with the implementation of the Process Writing method; what supporting and inhibiting factors influence its implementation according to both teachers and students; and how effective the Process Writing method is in improving students’ Arabic writing skills based on process-oriented and outcome-based evaluations. This research employs a descriptive qualitative approach to provide a comprehensive understanding of the implementation of the Process Writing method in Arabic writing instruction as reflected in teachers’ experiences and students’ responses. Primary data were obtained through classroom observations, in-depth interviews, and direct participation, while secondary data were collected from instructional documents. Data analysis involved data reduction, data display, and conclusion drawing, validated through source and method triangulation. The findings focus on instructional practices, teachers’ strategies, students’ experiences, and challenges encountered throughout the writing process. The results show that the Process Writing method is implemented systematically through stages ranging from pre-writing to publication, supported by instructional tools, model texts, scaffolding, and constructive feedback. Students respond positively, feeling guided and creatively engaged, although they still face challenges such as limited vocabulary, lack of confidence, and issues with accuracy. Supporting factors include teacher competence, student motivation, peer review, and the availability of media, while inhibiting factors involve limited time, linguistic constraints, psychological barriers, and technical issues. Overall, the method is effective in improving students’ writing abilities and fostering positive attitudes toward Arabic writing.